2021
DOI: 10.1021/acs.iecr.0c06278
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling of the Reactive Side in Large-Scale Fluidized Bed Boilers

Abstract: This work presents a dynamic model of the reactive side of large-scale fluidized bed (FB) boilers that describes the infurnace transient operation of both bubbling and circulating FB boilers (BFB and CFB, respectively). The model solves the dynamic mass and energy balances accounting for the bulk solids, several gas species, and the fuel phase. The model uses semiempirical expressions to describe the fluid dynamics, fuel conversion, and heat transfer to the furnace walls, as derived from units other than the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Most gas–solid fluidized bed systems adopt cyclone separators to collect the particles and maintain the material balance. As an indispensable component for the CFB boiler, the cyclone separator plays a major role in the stable operation, which is expected with high separation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Most gas–solid fluidized bed systems adopt cyclone separators to collect the particles and maintain the material balance. As an indispensable component for the CFB boiler, the cyclone separator plays a major role in the stable operation, which is expected with high separation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to steady-state modelling, fewer publications have been found regarding dynamic process simulation of the CFBs. Dynamic simulation, an extension of steady-state process simulation with time-dependence, offers an essential tool for the design of energy conversion, prediction of the transient behaviour of the combustion chambers, and process configurations under changing conditions (Alobaid et al, 2017;Castilla et al, 2021). A dynamic simulation model of a 750 MW el coal-fired power plant has been developed to evaluate the operation flexibility (Starkloff et al, 2015).…”
Section: Figurementioning
confidence: 99%
“…The results showed that the model can predict the load transient response very well. Castilla 28 presented a dynamic model of large-scale fluidized bed boilers to describe the steady-state and transient conditions. The fluidized beds are found to stabilize more rapidly to input changes when running at full load than at partial load.…”
Section: Introductionmentioning
confidence: 99%